Bank Credit and Aggregate Import Demand in South Africa: An Autoregressive Distributed Lag Approach - Ziramba, Emmanuel; Mumangeni, Johanna (European Scientific Journal, ESJ, 2017)
This study reformulated the aggregate import demand function for South Africa by incorporating a financial variable, bank credit. The study used the bounds testing approach for cointegration and the autoregressive distributed lag models to estimate short-run and long-run elasticities of aggregate import demand. The cointegration results confirm a long run relationship between the quantity of imports and the explanatory variables. Although bank credit has a positive impact on aggregate imports, it is statistically insignificant. It is statistically significant in the short-run. Our results suggest that bank credit is insufficient as a policy instrument for longterm import demand in South Africa. It can only be useful in managing the South African external balance in the short-run.